2004
DOI: 10.1002/ppul.10428
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ipratropium bromide plus fenoterol inhaled via Respimat® Soft Mist™ Inhaler vs. a conventional metered dose inhaler plus spacer in children with asthma

Abstract: The objective of this study was to compare the efficacy and safety of ipratropium bromide/fenoterol hydrobromide (IB/FEN; Berodual) delivered from the novel propellant-free Respimat Soft Mist Inhaler (SMI) with that from a chlorofluorocarbon (CFC) metered-dose inhaler (MDI) plus spacer in children with asthma. The study followed a multicenter, randomized, double-blind (within Respimat SMI), parallel-group design. During the 2-week run-in period, patients received two actuations of CFC-MDI tid (IB 20 microg/FEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…This review focused on identifying the prevalence of the use of different measures for defining asthma exacerbations, as well as the supporting evidence base. A total of 15 NIH-funded studies 18, 2027, 30, 31, 33, 3537 and 5 phase III industry-sponsored studies 11, 13, 1517 was identified that included children aged 5–11 years (with some variation in upper and lower age limits). Six additional studies included children aged 5–11 years together with adolescents.…”
Section: Specific Issues Related To Exacerbations As An Asthma Outcommentioning
confidence: 99%
“…This review focused on identifying the prevalence of the use of different measures for defining asthma exacerbations, as well as the supporting evidence base. A total of 15 NIH-funded studies 18, 2027, 30, 31, 33, 3537 and 5 phase III industry-sponsored studies 11, 13, 1517 was identified that included children aged 5–11 years (with some variation in upper and lower age limits). Six additional studies included children aged 5–11 years together with adolescents.…”
Section: Specific Issues Related To Exacerbations As An Asthma Outcommentioning
confidence: 99%
“…The cumulative dose study in adults with asthma (Kunkel et al 2000) concluded that IB/FEN delivered by Respimat was as effective as the CFC-pMDI at half the cumulative dose. Two Phase III studies were done comparing IB/FEN via Respimat and CFC-pMDI in adults and children with asthma (Vincken et al 2004; von Berg et al 2004). These studies concluded that delivery by Respimat instead of a CFC-pMDI allows a two- to four-fold reduction in dosage of IB/FEN while achieving similar efficacy.…”
Section: Effectiveness and Safety Of Devicementioning
confidence: 99%
“…These characteristics allow a higher proportion of the emitted dose to be delivered to the lungs than with pMDIs [11]. Bronchodilators delivered via Respimat SMI have proven clinical efficacy and safety in patients with asthma or chronic obstructive pulmonary disease (COPD) [12,13,14]. …”
Section: Introductionmentioning
confidence: 99%